The analysis of the spatio-temporal differentiation characteristics of total factor productivity of maize: Introducing the perspective of financial support - Lou, Sha (Frontiers in Environmental Science, 2022)
The problem we studied is the analysis of the spatio-temporal differentiation characteristics of total factor productivity of maize. The importance lies in that maize is one of the prominent grain crops in China, the improvement of maize production efficiency is helpful to guarantee the national food security. From the perspective of financial support, deepened the connotation of DEA model, this paper innovatively constructs the Global Malmquist index method, in view of the data of 13 major grain producing areas in China from 2007 to 2017, talks over the temporal evolution characteristics and spatial distribution modes of total factor productivity (TFP) of maize. The main results show that the TFP of maize production in China’s major grain producing areas is mostly of a high level between 2007 and 2017, revealing a fluctuating upward drift, with an average annual rate of increase of 10.7%. The conclusion we draw from the results is that as shown in the decomposition index, the variation of TFP of maize production mainly attributes to the shift of technological progress. In terms of space, the TFP of maize production in the central district is the highest, the eastern and western districts are relatively low.